Writing in the discipline of education: beliefs of future teachers regarding their academic literacy - Amo Sánchez-Fortún, José Manuel de; Baldrich, Kevin; Domínguez-Oller, Juana Celia; Pérez-García, Carmen (Frontiers in Education, 2024)
This study investigates the beliefs of future educators regarding academic literacy processes, focusing on the particularities associated with the Education disciplines. It examines how university students in Early Childhood Education and Primary Education degrees perceive the importance of communication skills, training in academic writing in discipline, and the suitability of teaching strategies in their academic and professional development. Using a quantitative descriptive approach, data were collected from a representative sample of 1000 Spanish university students through a validated questionnaire. The data were analysed using IBM SPSS Statistics 29.0.2.0 statistical software, and Chi-Square tests were conducted to determine the statistical significance of observed differences. The results highlight a dissonance between the importance students attribute to skills associated with academic literacy and the actual educational reality in university syllabi. Additionally, participants perceive relevant differences between academic writing in the education discipline, more closely linked to the development of reflective and research-oriented teachers in practice, and that of other areas of knowledge. In this regard, specific discursive genres considered most representative and necessary for professional teaching development have been identified. Based on the findings, recommendations are provided to enhance training in these areas, aiming to prepare educators for the evolving challenges of the educational environment.